Dinamika Pendidikan Kesehatan dengan Video Animasi Terhadap Pengetahuan Pemeliharaan Organ Reproduksi dan Pencegahan Sex Abuse Pada Anak Usia Sekolah - Handayani, Tri Lestari; Aini, Nurul; Anggiriani, Ika Rizki; Zahrina, Anissatul Fathinah Ayuniar (LPPM Institut Pendidikan Nusantara Global, 2024)
Knowledge of maintaining reproductive organs and preventing sex abuse in school-age children has a very important role in helping their knowledge about maintaining their reproductive health and preventing sexual crimes. Experimental with pre-test and post-test using animated videos. The sampling technique used was total sampling (32 respondents) class VIII-H at SMPN 9 Gresik. Data were collected using a knowledge questionnaire on maintaining reproductive organs and preventing sex abuse. Average knowledge before being given health education (52.02) and after being given health education (75.91). The average understanding of preventing sex abuse before being given health education (70.31) and after being given health education (82.50). The results of the paired t-test showed the influence of health education (animated videos) on knowledge of reproductive organ maintenance and preventing sex abuse at school age (pvalue 0.000). There is an influence of animated videos on knowledge of maintaining reproductive organs and preventing sex abuse in school-aged children at SMPN 9 Gresik.